The building of Brazilian Party System. New parties’s formation and political strategies - Vieira da Rocha, Décio; Cruz Pimentel, Paula (Estudios Internacionales, 2024)
This paper's main objective is to analyze the formation and success of new parties in the period of redemocratization and the return of Brazilian multipartyism (1979-2018). Although the phenomenon is recurrent in Brazil, few studies have looked more directly at the subject in Brazil. What are the determinants of the ongoing formation of new parties? Our hypotheses are that the permissiveness of the electoral system loses effect when actors adapt to it and that factors endogenous to political competition increase the likelihood of new parties emerging. We use previous methodologies and conceptualize new parties as those that are organizationally new (obtain a new registration) and win at least one seat in the Chamber of Deputies. We divided the parties into contestation or coaptation parties to assess the impact of institutional and economic variables on them. Our results indicate that parties that are totally "outside the system" (those of contestation) have more difficulty in becoming competitive, demonstrating that the phenomenon of the appearance of new acronyms is more linked to a strategic reorganization of the elites than to a demand from voters.